Imidazolium-based ionic liquids as additives to preserve the Enhanced Green Fluorescent Protein fluorescent activity - Veríssimo, Nathalia V. [UNESP] (2021)
Fluorescent Proteins (FP) can be applied as biomarkers and biosensors in the industrial and medical fields, but their large-scale use, especially for new industrial applications, is limited due to their low stability. Hence, the discovery of additives capable of preserving the activity of FP at room temperature and under stress conditions can help to expand and facilitate their commercial use. With this goal, we evaluated the application of 1-alkyl-3-methylimidazolium chloride-based ([Cnmim]Cl) ionic liquids (ILs) as additives to preserve the activity of Enhanced Green Fluorescent Protein (EGFP) at different storage times and under unfavorable conditions. All [Cnmim]Cl solutions (at 0.100 mol L−1) were able to preserve EGFP fluorescence for longer than the phosphate-saline buffer (PBS) and NaCl solutions, increasing its fluorescence manifestation from 1 to 3 months. [Cnmim]Cl with shorter to medium cationic alkyl chains were the most effective in preserving EGFP fluorescence. [Cnmim]Cl also protected EGFP activity in the presence of the surfactant SDS, the acid guanidine hydrochloride, and H2O2. Therefore, [Cnmim]Cl can be added to aqueous solutions to preserve EGFP fluorescence activity at room temperature for longer storage times and to reduce the negative impact of denaturing agents on EGFP. Therefore, there is a massive potential for the application of ILs as additives to preserve FP in the long-term without refrigeration and under unfavorable conditions, and this is fundamental to enable expansion of FP in industrial and commercial applications.